Effectiveness of a peer-refugee delivered psychological intervention to reduce psychological distress among adult Syrian refugees in the Netherlands: study protocol. Issue 1 (31st December 2020) - de Graaff, Anne M.; Cuijpers, Pim; Acarturk, Ceren; Bryant, Richard; Burchert, Sebastian; Fuhr, Daniela C.; Huizink, Anja C.; de Jong, Joop; Kieft, Barbara; Knaevelsrud, Christine; McDaid, David; Morina, Naser; et al.
ABSTRACT: Background : Syrian refugees face multiple hardships and adversities which put them at risk for the development of mental health problems. However, access to adequate mental health care in host countries is limited. The WHO has developed Problem Management Plus (PM+), a brief, scalable psychological intervention, delivered by non-specialist helpers, that addresses common mental disorders in people affected by adversity. This study is part of the STRENGTHS project, that aims to evaluate peer-refugee delivered psychological interventions for Syrian refugees in Europe and the Middle East. Objective : To evaluate the effectiveness and cost-effectiveness of the peer-refugee delivered PM+ intervention among Syrian refugees with elevated levels of psychological distress in the Netherlands. Methods : PM+ will be tested in a randomized controlled trial (RCT) among Arabic-speaking Syrian refugees in the Netherlands aged 18 years and above with self-reported psychological distress (Kessler Psychological Distress Scale; K10 >15) and impaired daily functioning (WHO Disability Assessment Schedule; WHODAS 2.0 >16). Participants (N = 380) will be randomized into care as usual with PM+ (CAU/PM+, n = 190) or CAU only (CAU, n = 190). Baseline, 1-week post-intervention, and 3-month and 12-month follow-up assessments will be conducted. Primary outcomes are symptoms of depression and anxiety. Secondary outcomes are functional impairment, posttraumatic stress disorder symptoms, self-identified problems, anger, health and productivity costs, and hair cortisol concentrations. A process evaluation will be carried out to evaluate treatment dose, protocol fidelity and stakeholder views on barriers and facilitators to implementing PM+. Results and Conclusions : PM+ has proved effectiveness in other populations and settings. After positive evaluation, the adapted manual and training materials for individual PM+ will be made available through the WHO to encourage further replication and scaling up. Trial registration : Trial registration Dutch Trial Registry, NL7552, registered prospectively on March 1, 2019. Medical Ethics Review Committee VU Medical Center Protocol ID 2017.320, 7 September 2017.